Modified rock stress factor for the Mathews stability graph method and its application - Minsi Zhang; Heng Liu; Yong Yang; Jiong Wei; Wenhua Zha (Geomatics, Natural Hazards & Risk)
It is difficult to accurately predict and assess the instability of the stope. This article uses the improved Mathews stability graph method to scientifically analyse and evaluate the quality and stability of the surrounding rock. It utilizes the failure factor (FF) to express the degree of rock failure under different stress states based on the Mohr–Coulomb criterion and to determine the new rock stress factor. This new method is successfully applied in a case study at a lead–zinc mine in Hongling and makes a comparative analysis with the actual situation of the site.